A sustainable enterprise content management technologies use framework supporting agile business processes - Arshad, N.I. (Taylor and Francis Ltd., 2021)
Organisations invest in a considerable number of resources towards implementing Enterprise Content Management Systems (ECMS), expecting productive outcomes from the ECMS utilisation. A well-designed ECMS is impressive and deserves admiration, but to the organisations the ECMS limited value is often a major highlight. This motivates this study to understand how sustainable investment in Enterprise Content Management (ECM) technologies could support organisational Agile Business Processes (ABP). In studying how different organisation types utilise ECMS, the research employs a cross-sectional multiple-case studies approach with participation of seven large-scaled organisations. An investigation and an exploration into how these organisations interacted with ECMS are pivotal to the research. Based on the qualitative data analysis, this study proposes a sustainable ECMS-use framework that explains how ABP could benefit from it. Essentially, the framework enlightens researchers and practitioners to leverage ECM technologies for different work practices supporting ABP and organisational structures. Â© Operational Research Society 2021.